DIPG-29. PHOSPHATIDYLINOSITOL-4, 5-BISPHOSPHATE 3-KINASE (PI3K) INHIBITION DRIVES PROTEIN KINASE C ACTIVATION (PKC) IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (4th December 2020) - Duchatel, Ryan J; Mannan, Abdul; Jackson, Evangeline R; Staudt, Dilana; Skerrett-Byrne, David A; Jamaluddin, M Fairuz B; Woldu, Ameha S; Douglas, Alicia; Hulleman, Esther; Carcaboso, Angel M; Monje, Michelle; Alvaro, Frank; et al.
Abstract: Recurring somatic mutations and gene amplifications to members of the phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) signaling axis are overarching contributors to the aggressive growth and survival of diffuse intrinsic pontine gliomas (DIPG). However, targeting PI3K has thus far failed to improve outcomes for patients in the clinic. To identify the mechanisms underpinning PI3K/AKT/mTOR treatment failure in DIPG, we have employed high-resolution quantitative phosphoproteomic profiling in patient-derived DIPG cell lines harboring H3K27M and PI3K mutations, +/- the blood-brain barrier permeable PI3K inhibitor, paxalisib (previously "GDC-0084", currently in Phase I trials - NCT03696355) and rapamycin. Paxalisib was significantly more potent than rapamycin at inducing PI3K/AKT/mTOR inhibition, however, both simultaneously activated protein kinase C signaling ( pT500 PKCβ +8.2 and +4.5 fold, respectively). PKC lies directly upstream of myristoylated alanine-rich C-kinase substrate (MARCKs), which was phosphorylated at Ser170 by +9.4 and +4.7 fold, respectively; promoting actin cytoskeletal remodeling and cellular migration. Indeed, activation of PKC signaling using phorbol 12-myristate 13-acetate (PMA), increased DIPG cell growth and migration by >3 fold. Targeting PKC using midostaurin (FDA-approved for acute myeloid leukemia), and enzastaurin (blood-brain barrier penetrant inhibitor of PKCβ), in combination with paxalisib was highly synergistic (CI=<0.9), reducing proliferation and driving apoptosis. Mechanistically, compensatory activation of PKC signaling following PI3K inhibition was regulated by the accumulation of Ca +2 ions, as chelation using BAPTA-AM significantly reduced PKC activity following PI3K inhibition. These data highlight the power of phosphoproteomic profiling for the rational design of drug combination strategies, which need to be tested in vivo prior to clinical trials for DIPG.